2016
DOI: 10.1007/s00705-016-2857-0
|View full text |Cite
|
Sign up to set email alerts
|

First detection of bluetongue virus serotype 14 in Poland

Abstract: Here, we present the first detected cases of bluetongue virus (BTV) in native cattle from Poland. The virus was found in animals located near the Polish-Belarusian and Polish-Lithuanian borders. The positive animals were detected through an official epidemiological surveillance program. A combination of type-specific real-time RT-PCR and phylogenetic tests revealed the presence of BTV serotype 14 (BTV-14). This serotype is highly homologous to the vaccine strain and BTV-14 present in Russia, Lithuania, and Spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 9 publications
1
26
0
2
Order By: Relevance
“…BTV‐14 infection was confirmed in four European bison from Białowieża Primeval Forest and in cattle in the neighbouring region of Sokółka by real‐time RT‐PCR at the Pirbright Institute (Krzysiak, unpublished data; Pirbright Institute, ). The same homologous to South African vaccine BTV‐14 strain virus has been observed circulating in this area between 2011 and 2014 (Orłowska et al., ). The virus was also isolated in KC4 ( C. sonorensis ‐derived cell line) and BHK1 (baby hamster kidney) cells (http://www.reoviridae.org/dsrna_virus_proteins/reoid/btv-14.htm).…”
Section: Discussionmentioning
confidence: 65%
“…BTV‐14 infection was confirmed in four European bison from Białowieża Primeval Forest and in cattle in the neighbouring region of Sokółka by real‐time RT‐PCR at the Pirbright Institute (Krzysiak, unpublished data; Pirbright Institute, ). The same homologous to South African vaccine BTV‐14 strain virus has been observed circulating in this area between 2011 and 2014 (Orłowska et al., ). The virus was also isolated in KC4 ( C. sonorensis ‐derived cell line) and BHK1 (baby hamster kidney) cells (http://www.reoviridae.org/dsrna_virus_proteins/reoid/btv-14.htm).…”
Section: Discussionmentioning
confidence: 65%
“…Sequencing of the VP2 (Seg-2) and NS1 (Seg-5) genes resulted in the Russian BTV-14 strain being grouped with a vaccinelike BTV-14 strain used in African countries (Figure 2). In addition to these findings, a related BTV-14 strain was also documented in Poland in animals near the Polish-Belarusian and Polish-Lithuanian borders in 2012 (47). Notably, Russian strain G244/11, strain SPA2012/01 detected in cattle in Spain imported from Lithuania, and Polish strain POL2012/01 shared approximately 99.9% identity based on the VP2 gene.…”
Section: Discussionmentioning
confidence: 67%
“…The serendipitous detection of BTV-14 in the cattle in the Smolensk region in 2011-2012 represents the first historical incidence of BTV in the European part of Russia in which antibodies and live viruses were identified in local livestock. The circulation of the live virus was confirmed by detection of BTV-14 in the neighboring Smolensk and Kaluga regions in 2012 (Figure 1, Table 2), as well as in Poland in 2012 and 2014 (47).…”
Section: Discussionmentioning
confidence: 76%
“…As the virus has not been isolated from any of the PCR-positive samples, it can be concluded that the BTV-positive animals were probably in the late stages of infection, when animals remain PCR-positive, but are unlikely to be infective to midges. Recently, the first cases of BTV detected in native cattle from Poland have been described (33). In the National Reference Laboratory for Bluetongue, BTV serotype 14 was detected by type-specific rRT--PCR in animals reared near the Polish-Belarusian and Polish-Lithuanian borders.…”
mentioning
confidence: 99%
“…In the National Reference Laboratory for Bluetongue, BTV serotype 14 was detected by type-specific rRT--PCR in animals reared near the Polish-Belarusian and Polish-Lithuanian borders. It was suggested that the most probable route of BTV introduction into Poland was transmission through Culicoides midges (33).…”
mentioning
confidence: 99%